A 3D petrographic analysis for concrete freeze-thaw protection. (February 2020) - Song, Yu; Damiani, Robbie M.; Shen, Chuanyue; Castaneda, Daniel I.; Lange, David A.
Abstract: Petrographic analysis is routinely implemented to measure air void parameters for predicting freeze-thaw durability of concrete. The 1D or 2D measurements obtained from polished concrete sections are used to infer 3D protection of the paste. Since an arbitrary point in a section view may be partially protected by air voids that are not intersected, a stereological model is proposed to consider both intersected and un-intersected voids. The model is tested with a group of concrete mixtures with varying air entrainment, mix proportion, and aggregate type. As compared with the 2D analysis, this 3D analysis indicates a higher percent of cement paste being protected. When equating the protection range to Powers' spacing factor, it is found that roughly 98% of paste is protected in 3D. Findings in this study also align with results obtained by other authors using numerical simulation and computed tomography. This model offers a realistic concrete freeze-thaw assessment.